Pengaruh Motivasi Kerja terhadap Kinerja Pegawai Dinas Kementerian Kelautan dan Perikanan Kabupaten Kepulauan Mentawai - Febsri Susanti; Hari Novrizal Putra (JURNAL PUNDI, 2019)
Performance is a general description of the level of achievement of the implementation of a program activity, wisdom in realizing the suggestions, goals, vision and mission of the organization / agency, then between performance and motivation have a very close relationship because a person's performance is determined by one's ability to carry out tasks given well and able to be responsible for carrying out work. This research was conducted at the Mentawai Islands District Ministry of Maritime Affairs and Fisheries by using a sample of 45 people with sample selection. In this study using the Total Sampling technique, namely by taking the entire population as a sample as long as the population is known to be limited. With data analyzed by multiple linear regression analysis techniques. Motivation affects performance significantly and positively for employees of the Ministry of Maritime Affairs and Fisheries of the Mentawai Islands Regency. It can be concluded that the higher the motivation of an employee, the performance will also increase. Keywords:Work Motivation, Employee Performance